A Role Theory Perspective on How and When Goal-Focused Leadership Influences Employee Voice Behavior - Qian, Jing; Li, Xiaoyan; Wang, Bin; Song, Baihe; Zhang, Wei; Chen, Meng; Qu, Yi (Frontiers in Psychology, 2018)
Despite an increasing number of studies that identify leaders’ role in promoting employees’ voice behavior, little is known about the role that supervisors’ goal-focused leadership plays in this. The current study aims to address this research gap by using the role theory to explain how supervisors’ goal-focused leadership influences employees’ voice behavior and the conditions under which supervisors’ have maximum impact on employee voice. A field study of 197 employees and their immediate supervisors offered support for our model. The results indicated a positive association between goal-focused leadership and employees’ voice behavior that was mediated by leaders’ omission of rewards and punishments. We also found that perceived helping and support from coworkers positively moderated the relationship between leaders’ reward and punishment omission and employees’ voice behavior such that the relationship was weaker when coworker helping and support was higher. The findings provide more comprehensive picture of the process by which goal-focused leadership influences employee voice and highlight how coworkers can buffer the negative effect of ineffective managerial reward and punishment omission. The practical implications of this research, its limitations and directions for future research are also discussed.